2010
DOI: 10.1016/j.jtbi.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Caught between two Allee effects: Trade-off between reproduction and predation risk

Abstract: Abstract:Reproductive activities are often associated with conspicuous morphology or behaviour that could be exploited by predators. Individuals can therefore face a trade-off between reproduction and predation risk. Here we use simple models to explore population-dynamical consequences of such a trade-off for populations subject to a mate-finding Allee effect and an Allee effect due to predation. We present our results in the light of populations that belong to endangered species or pests and study their viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…In conclusion, a number of modelling studies have shown that a predation-driven Allee effect may occur in theory, and also a wide range of studies on animals have confirmed this mechanism [6,14,[18][19][20]. However, there has been little evidence of predation-driven Allee effects in plants, and our study provides strong evidence of a component Allee effect driven by predispersal seed predation in a plant species.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In conclusion, a number of modelling studies have shown that a predation-driven Allee effect may occur in theory, and also a wide range of studies on animals have confirmed this mechanism [6,14,[18][19][20]. However, there has been little evidence of predation-driven Allee effects in plants, and our study provides strong evidence of a component Allee effect driven by predispersal seed predation in a plant species.…”
Section: Discussionsupporting
confidence: 66%
“…Apart from pollination, predation is another factor affecting reproductive success, which is also density dependent. Therefore, whether plant density has a net positive or negative effect on the realized reproductive success depends on the relative strengths of pollination success and predispersal seed predation [13][14][15][16][17]. For example, decreased predation at low density counterbalanced the disadvantages of low-pollination success, and thus the final output was not detected as density dependent in Acer mono [17].…”
Section: Discussionmentioning
confidence: 99%
“…Other processes that may influence individual fitness include Allee effects, that is, a decrease in fitness caused by a decrease in population size (Stephens et al ., ). Predation is one of the numerous drivers of Allee effects that have been recently documented in animal populations (Gascoigne & Lipcius, ; Kramer & Drake, ; McLellan et al ., ; Pavlová et al ., ; Bourbeau‐Lemieux et al ., ; Kang et al ., ) but similar evidence is scarce in plants. Still, Xia et al .…”
Section: Impacts Of Predispersal Insect Herbivory On Reproductive Strmentioning
confidence: 99%
“…Such energy expenditure might similarly impoverish their physical condition (Fleming and Nicolson 2004;Schubert et al 2009). In addition, courtship behavior makes male lizards more conspicuous to predators (Koga et al 2001;Pavlová et al 2010), which might also result in decreased survival rates.…”
Section: Introductionmentioning
confidence: 99%